Use of granulocyte colony-stimulating factor in patients with chemotherapy-induced neutropaenia - Lucky L. Shokane; Selente Bezuidenhout; Maryke Lundie (AOSIS, 2023)
Background: Febrile neutropaenia (FN) and resultant infections are the major cause of treatment-related morbidity and mortality in patients receiving chemotherapy. Clinical practice guidelines recommend the use of granulocyte colony-stimulating factors (G-CSF) to reduce the risk of FN and ensuing complications in patients receiving chemotherapy. Despite these recommendations, inappropriate usage of G-CSF has been reported. Aim: To assess prescribing patterns and adherence to international guidelines of G-CSF in adult patients with chemotherapy-induced neutropaenia (CIN) at the haematology oncology wards of the Dr George Mukhari Academic Hospital (DGMAH) and compliance to guidelines. Methods: Medical records of adult patients who received G-CSF were reviewed retrospectively between 01 January 2018 and 31 July 2018. Results: Of the 128 patient files screened, 57 cases met the inclusion criteria. Duration of treatment with G-CSF was not in accordance with guidelines in more than 50% of the patients and in 43.86%, G-CSF dosing deviated from recommended guidelines. Conclusion: The study demonstrated over-prescribing of G-CSF due to either increased doses or duration of G-CSF therapy. Although prescribed for the correct indication, the dosage was often too high or the duration was too long, even once an acceptable neutrophil nadir count was reached. Interventions to optimise the use of G-CSF are required and the pharmacist may play a role in this regard. Contribution: The administration of the correct doses of G-CSF can reduce both the severity and duration of neutropaenia. Over-prescribing and incorrect dosing may contribute to patient morbidity and add to the financial burden of healthcare.